Opening Gambit The London season kicks off with Le Corsaire reviewed - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Opening Gambit. Review of the London season kicks off with Le Corsaire. Enjoyably old-fashioned entertainment, the equivalent of a pantomime or Saturday morning matinee at the cinema. PALABRAS CLAVE: Kirov, Le Corsaire.
Dentro del apartado "Kirov 2003".